Pengendalian Persediaan Bahan Baku Batu Bara Menggunakan Metode Min-Max Di PT. XYZ - Heru Winarno; Syahrul M Dhani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Inventory is an important factor in carrying out a production. Many companies experience problems in terms of inventory control, one example is inventory scarcity. The purpose of this study is to optimize the need for goods so that the company will not experience problems with inventory shortages or inventory buildup. This study uses the Min-Max method by collecting data in the form of inventory of goods needs, ordering costs, and storage costs. The result of this study is that the safety stock value of 80,887-tons is useful for protecting and anticipating inventory shortages, so companies must be on guard when they are at that value. Then, the Reorder Point value was obtained at 108,165 tons. Furthermore, the value of the Minimum Inventory is 269,879-tons and the Maximum Inventory is 378,044-tons so that companies are not recommended to have more inventory than that value.